2D investigation of water permeability in hydrate-bearing sediment with coexisting hydrate growth habits. (4th May 2020) - He, Gaofeng; Luo, Xianqi; Shakya, Chandan
Abstract: Permeability variation in the presence of hydrates plays an important role in hydrate dissociation and may lead to extraction issues. Therefore, a wide range of pore-scale studies considering the hydrate growth habit have been conducted by various researchers. Here, we use microscopic training images of hydrate-bearing sediment to replicate the micromorphology of hydrates and coexisting hydrate growth habits (pore filling and coating) into 2D reconstruction models by multiple point statistics (MPS). Accounting for the geometric differences between each realisation and the different ratios between coating hydrate and pore-filling hydrate, permeability simulation is performed by the lattice Boltzmann Method (LBM). Results show that subtle geometric differences of hydrates may result in great changes in permeability for a given hydrate saturation for the same hydrate growth habit. The Kozeny–Carman model for single hydrate growth habit can also be used for the hydrate-bearing sediment with coexisting hydrate growth habits if the ratio of these two hydrate saturations is about 4, where the effect of coating or pore-filling hydrate can be neglected. This reconstruction model agrees well with experimental results and can be easily implemented in reservoir simulators for complex hydrate distributions.